Profile of poisonings due to indiscriminate use of antidepressants in adolescence (Research, Society and Development, 2023)
Depression is an important public mental health problem worldwide, being defined as a mental disorder linked to social, biological and pathological factors, which can directly impact the functional and social capabilities of the individual, and is even an important risk factor for suicide. In adolescence, this is an increasingly common health problem, often associated with some type of trauma, which leads this population to adopt self-medication strategies with antidepressants to alleviate symptoms, without professional guidance, favoring the emergence of reactions of drug poisoning. The objective of the present study was to carry out a literature review to identify the profile of intoxication among adolescents, due to the use of antidepressant pharmacological substances. A qualitative research of the integrative review type was carried out, with a sample selected from the VHL, LILACS and SCIELO databases. The main causes associated with poisoning due to antidepressant medications were linked to attempted suicide, as a strategy used by adolescents to deal with their psychological suffering. Therefore, the pharmacist acts on the front line in preventing these events, precisely because he is a professional with in-depth knowledge about the medicine.